Ciało i Krew Jezusa jako pokarm. J 6,48–58 w interpretacji Klemensa Aleksandryjskiego - Słomka, Jan (Śląskie Studia Historyczno-Teologiczne, 2004)
The words of Jesus about his Body and Blood given to us as nourishment are interpreted by Clement as a promise that the Logos will provide our souls with all necessary food. Such interpretation is open to the Eucharist, it must be noted, however, that the word „Eucharist” does not occur in the quoted texts. Clement remains at the level of allusion. His thought seems to suggest that Jesus’ words should be interpreted as predicting complete cognition and direct perception, an ultimate purpose for each gnostic. It should also be mentioned that interpretations open to the Eucharist appear only in Paedagogus, in the context of the on-going debate within the Church of Alexandria, concerning, among others, the criteria of participation in the Eucharist. In Stromata, Clement gives an entirely spiritual meaning to the words of Jesus: they predict full contemplation of the Logos, which here on Earth is available only to a few, but will be perfectly fulfilled in the world to come.